Mechanism of IFITM1 regulating epidural scar hyperplasia after laminectomy through SMAD3/CBR4 pathway - Wang, Haoran; Zhu, Zekai; Liu, Jun (Frontiers in Immunology, 2025)
BackgroundEpidural scar hyperplasia is a prevalent complication post-laminectomy, contributing significantly to persistent low back pain and other symptoms, ultimately undermining surgical outcomes. Previous studies have identified fibroblast proliferation and differentiation, as well as adipocyte fibrosis, as central to this process, though the precise mechanisms remain elusive.MethodsA model of laminectomy was established using wild-type mice and IFITM1-KO mice. Methods such as HE staining and Masson staining were employed to assess the degree of fibrosis in the postoperative wound area of the mice. Immunofluorescence and Western blot were performed to verify the localization of IFITM1 and fibronectin. NIH-3T3 fibroblast cells and primary fibroblast cell models were established, and immunoblotting was used to detect changes in the expression levels of fibronectin, P-smad3, smad3, and IFITM1. Subsequently, co-immunoprecipitation was conducted to preliminarily demonstrate that CBR4 is a related protein of IFITM1. The amounts of adipose tissue and CBR4 in the postoperative wound area were compared between wild-type and IFITM1-KO mice in the laminectomy model. CBR4 localization was examined using immunofluorescence, followed by the establishment of an in vitro adipocyte model, where Oil Red O staining and other methods were utilized to confirm the process of adipocyte fibrosis and the roles of IFITM1/CBR4 therein.ResultsIn a murine laminectomy model, fibroblast proliferation, activation, and adipocyte fibrosis were found to exacerbate epidural scar formation. IFITM1, a critical protein regulating cell proliferation, is expressed in fibroblasts. The proliferation and activation of fibroblasts, characterized by high IFITM1 expression, were inhibited by suppression of the SMAD3 signaling pathway. In vivo studies revealed a reduction in epidural fibrosis following laminectomy in the absence of IFITM1. Additionally, CBR4, a protein associated with IFITM1 and involved in fatty acid synthesis, showed reduced expression in adipocytes under inflammatory conditions, triggering their transformation into fibroblasts, a process regulated by IFITM1. Our animal experiments also confirmed the presence of adipose tissue within epidural scars, with IFITM1 deficiency correlating with reduced adipose tissue and increased CBR4 expression. ConclusionThese findings demonstrate that IFITM1 inhibits fibroblast proliferation and differentiation via SMAD3 signaling suppression and modulates adipocyte fibrosis by regulating CBR4 expression, thereby influencing epidural scar hyperplasia post-laminectomy.